The Dynamics of Asymmetric Competition in the Healthcare Industry: Analysis of Market Structure and Non-Price Strategies at XYZ Regional General Hospital and Reksa Waluya Hospital - Galih Fendi Christianto (Eduvest - Journal of Universal Studies, 2026)
The healthcare industry in Mojokerto City demonstrates competitive dynamics between public and private hospitals influenced by the tariff regulations of the National Health Insurance (Jaminan Kesehatan Nasional [JKN]). RSUD, as a public hospital, has a cost advantage through government subsidies, creating asymmetric competition with private hospitals such as RS Reksa Waluya. This research aims to analyze the dynamics of asymmetric competition between RSUD XYZ and RS Reksa Waluya and to identify competitive strategies that can support the sustainability of private hospitals. This research employs a managerial economics approach using a comparative case study method involving two hospitals in Mojokerto City to analyze market structure and competitive strategies. The results indicate that the hospital market structure is hybrid, combining characteristics of monopolistic competition and oligopoly. RSUD has an absolute cost advantage, making price-based competition ineffective for RS Reksa Waluya. Competition has shifted from monetary pricing strategies toward non-price factors, such as waiting time efficiency, the adoption of Electronic Medical Records (EMRs), value-based branding, and service specialization, including geriatric care. The sustainability of private hospitals depends more on service differentiation and operational efficiency strategies, while public hospitals should focus on improving managerial efficiency to maintain service quality.